Analyzing oxygen transport resistance and Pt particle growth effect in the cathode catalyst layer of polymer electrolyte fuel cells. (5th May 2020) - Gwak, Geonhui; Lee, Jaeseung; Ghasemi, Masoomeh; Choi, Jaeyoo; Lee, Seung Woo; Jang, Seung Soon; Ju, Hyunchul
Abstract: The oxygen transport resistance in the cathode catalyst layer (CL) of polymer electrolyte fuel cells (PEFCs) has been reported to be significantly higher than expected, especially when the platinum (Pt) loading is low and/or the degree of CL degradation is severe. In this paper, the oxygen transport resistance behavior in the cathode CL is numerically analyzed under various CL design and operating conditions. Particular emphasis is placed on the aged CL wherein Pt particle growth and active Pt surface area loss are observed. For this study, a previously developed micro-scale catalyst model is improved upon to account for Pt particle size. The new model includes calculations of catalyst activity and electrochemically active surface areas, as well as various transport resistances through the ionomer and liquid films. After coupling the micro-scale CL model with a three-dimensional PEFC model, multi-scale simulations are carried out under various PEFC catalyst designs (varying Pt loading, ionomer fraction, oxygen permeation rate through the ionomer film) and operating conditions (drying or flooding of the electrode, high or lower current density). The simulation results agree well with experimental oxygen transport resistance data and further indicate that CL design with low Pt loading is more susceptible to degradation. Providing extensive multi-dimensional contours of species concentration, temperature, and current density inside the PEFC, this study provides a comprehensive understanding of oxygen transport resistance in the cathode CL in different PEFC situations. Highlights: A microscale catalyst layer model is newly developed and coupled with a three-dimensional macroscale fuel cell model. The oxygen transport behavior inside the microstructure of cathode catalyst layer is analyzed. Improvement of oxygen diffusivity in the ionomer film is critical under low Pt loading conditions. Thick CL or using bare carbon particles helps to reduce the oxygen transport resistance.